Strategic silences, eroded trust: The impact of divergent COVID-19 vaccine sentiments on healthcare workers' relations with peers and patients. Issue 4 (23rd January 2023) - Heyerdahl, Leonardo W; Dielen, Stef; Dodion, Hélène; Van Riet, Carla; Nguyen, ToTran; Simas, Clarissa; Boey, Lise; Kattumana, Tarun; Vandaele, Nico; Larson, Heidi J.; Grietens, Koen Peeters; Giles-Vernick, Tamara; et al.
Highlights: Healthcare workers report difficulties discussing vaccines with peers and patients. Vaccine skeptical healthcare workers fear inducing patient anxieties or complaints. In scarce resource contexts unvaccinated Covid-19 patients can face suboptimal care. This difficult climate threatens peer and patient trust relationships. Abstract: Background: Polarized debates about Covid-19 vaccination and vaccine mandates for healthcare workers (HCWs) challenge Belgian HCWs ability to discuss Covid-19 vaccine sentiments with peers and patients. Although studies have identified drivers of HCWs vaccine hesitancy, they do not include effects of workplace interactions and have not addressed consequences beyond vaccine coverage. Methods: Interviews and focus group discussions with 74 HCWs practicing in Belgium addressed Covid-19 vaccine sentiments and experiences of discussing vaccination with peers and patients. Results: Most participating HCWs reported difficulties discussing Covid-19 vaccination with peers and patients. Unvaccinated HCWs often feared that expressing their vaccine sentiments might upset patients or peers and that they would be suspended. Consequently, they used social cues to evaluate others' openness to vaccine-skeptical discourses and avoided discussing vaccines. Surprisingly, some vaccine-confident HCWs hid their vaccine sentiments to avoid peer and patient conflicts. Both vaccinated and unvaccinated HCWs observed that unvaccinated patients occasionally received suboptimal care. Suboptimal care was central in unvaccinated HCW unwillingness to express their vaccine sentiments to peers. Both vaccinated and unvaccinated HCWs described loss of trust and ruptured social relations with peers and patients holding divergent vaccine sentiments. Discussion: Belgian HCW perceived Covid-19 vaccines as a risky discussion topic and engaged in "strategic silences" around vaccination to maintain functional work relationships and employment in health institutions. Loss of trust between HCW and peers or patients, along with suboptimal patient care based on vaccination status, threaten to weaken Belgium's, and by implication, other health systems, and to catalyze preventable disease outbreaks.